Bioindicadores filogenéticos para predição dos enterotipos do microbioma intestinal humano - Veras, Henrique César Teixeira (2013)
Humans live in constant association with microorganims. The amount of microorganims present in the human body exceeds our own cell number. That community of microorganisms has deep influence in health and disease. The use of high-throughput DNA sequencing technologies and culture independent approaches have been enlarging the understanding concerning the communities of microorganisms and the association of these with the host. The human gastrointestinal tract contains one of the most complex bacterial communities. It was proposed recently that the microbiome can be classified in three enterotypes. In our study, we used data metagenomics quantitative search to identify phylogenetic patterns in the intestinal microbiome to develop prediction models for the enterotypes. To reach this aim, statistical tests were applied to the data regarding abundance of bacteria in level taxonomic corresponding to genus. We identified genus significantly with the abundance different and important correlations. Besides the ratio among genus to be used as parameter bioindicator of the respectives enterotypes. Through the logistic regression test we identified that the prediction model for ET1 was influenced significantly by the ratio of Bacteroides / (Prevotella + Ruminococcus). In the model for prediction of ET2, it was the ratio of Prevotella / Bacteroides with such as characteristic significance. And for the model of ET3, we identified the ratio of (Akkermansia + Alistipes) / (Bacteroides + Prevotella) as significant parameter. These models were assessed against two groups of independent data and associated with the value of cut-off 5%; 20% and 95% respectively. Besides the value of cutoff for each models, the crossed validation allowed the association of the model with the measures of PPV for ET1, specificity for ET2 and PNV for ET3. We propose the experimental validation of these models for the qPCR technique. And with that methodology established, it would be possible to do the diagnosis of the enterotype individually.